How RA Associated HLA-DR Molecules Contribute to the Development of Antibodies to Citrullinated Proteins: The Hapten Carrier Model - Roudier, Jean; Balandraud, Nathalie; Auger, Isabelle (Frontiers in Immunology, 2022)
The risk to develop rheumatoid arthritis (RA), the most destructive type of autoimmune arthritis, is carried by HLA-DRB1 alleles containing a 5 amino acid motif: the shared epitope (SE). RA is preceded by the emergence of disease specific anti citrullinated protein antibodies (ACPA). SE positive HLA-DRB1 alleles are associated with ACPA and ACPA positive RA, not with ACPA negative RA, suggesting they contribute to RA through ACPA. Understanding how HLA-DRB1 genotypes influence ACPA could lead to a curative or preventive treatment of RA. The "Shared epitope binds citrullinated peptides " hypothesis suggests that RA associated HLA-DR alleles present citrullinated peptides to T cells that help ACPA producing B cells. The "Hapten carrier model" suggests that PAD4 is the target of the T cells which help ACPA specific B cells through a hapten carrier mechanism in which PAD4 is the carrier and citrullinated peptides are the haptens. Direct binding assay of citrullinated peptides to purified HLA-DR molecules does not support the "shared epitope binds citrullinated peptides" hypothesis. The Odds Ratios to develop ACPA positive RA associated with each of 12 common HLA-DRB1 genotypes match the probability that the two HLA-DR molecules they encode can bind at least one peptide from PAD4, not from citrullinated fibrinogen. Thus, PAD4 tolerization might stop the carrier effect and switch off production of ACPA.